PROFIL MASYARAKAT PERIKANAN DAN ALAT TANGKAP IKAN DI WADUK JATIGEDE - Muhammad Ismail Yusuf Yusuf; Junianto Junianto (Jurnal Perikanan Unram, 2024)
The construction of Jatigede Reservoir caused a change in the profession of the community from farmers to fishermen. This study aims to analyze the profile of fisheries communities and fishing gear in Jatigede Reservoir. This research used survey method with purposive random sampling. The research locations included Cisitu, Wado, Darmaraja, Jatigede and Jatinunggal sub-districts. The results showed that the fisheries community around Jatigede Reservoir consisted of 54% fishermen, 34% cultivators and 12% processors. The dominant fishing gear used by the Jatigede Reservoir fishery community is the spread net (77%), followed by fishing hooks (22%), and anco (1%). The most common type of fish caught is Nile Tilapia. Fishermen's preferences in choosing fishing gear are based on technical, socio-cultural and official rules.